Odpowiedzi

Najlepsza Odpowiedź!
2010-03-18T20:06:54+01:00
1.)

2(x-3/4x+2)= 3(x+1)-6
2x-1,5x+4=3x+3-6
0,5x+4=3x-3 |-3x
-2,5x+4= -3 |-4
-2,5x= -7 |:(-2,5)
x= 2,8

2.)

2(x-3)+(x+4)(x-2)= (x-1)(x+3)+1
2x-6+x²-2x+4x-8=x²+3x-x-3+1
4x+x²-14=x²+2x-2 |-x²
4x-14=2x-2 |-2x
2x-14= -2 |+14
2x=12 |:2
x=6

3.)

|x-6|+4> 2(x-4)
x-6+4>2x-8 |-2x
-x-2> -8 |+2
-x> -6 |:(-1)
x<6
2010-03-18T20:12:52+01:00
1.
2[x-3/2(2x +1)] = 3x+ 3-6
x-3/2x +1 = 3x - 3 /(2x + 1)
x- 3+ 6x2 + 3x - 6x - 3
6x2 - 4x = 0
2x(3x- 2) = 0
x= 0 ∨ x= ⅔

2.
2x - 6x2 - 2x + 4x - 8= x2 +3x - x - 3 +1
x2 + 4x - 14 = x2 + 2x - 2
2x = 12
x = 6

3.
/x-6/ > 2x - 12
x - 6 >2x - 12 ∨ x - 6< 12 - 2x
x<6